A Mixed-Method Study of Practitioners’ Perspectives on Issues Related to EHR Medication Reconciliation at a Health System - Rangachari, P. (Qual Manag Health Care, 2019)
BACKGROUND: In an effort to reduce medication discrepancies during transitions-of-care and improve accuracy of the patient’s medication list, AU Health conducted a study to identify a comprehensive set of issues related to EHR Medication Reconciliation (MedRec) from the perspective of practitioners directly involved in the EHR MedRec process. METHODS: An exploratory mixed-method design was used. The two-round study included 15 individual interviews, followed by a survey of 200 practitioners, i.e., physicians, nurses, and pharmacists, based in the outpatient and inpatient medicine service at AU Health. RESULTS: Thematic analysis of interview data identified 55 issue-items related to EHR MedRec under 9 issue-categories. The survey sought practitioners’ importance-rating of all issue-items identified from interviews. A total of 127 (63%) survey responses were received. Factor analysis served to validate the following 6 of the 9 issue-categories, all of which, were rated “Important” or higher (on average), by over 70% of all respondents: 1) Care-Coordination (CCI); 2) Patient-Education (PEI); 3) Ownership-and-Accountability (OAI); 4) Processes-of-Care (PCI); 5) IT-Related (ITRI); and 6) Workforce-Training (WTI). Significance-testing of importance-rating by professional affiliation revealed no statistically significant differences for CCI and PEI; and some statistically significant differences for OAI, PCI, ITRI, and WTI. CONCLUSION: There were two key gleanings from the issues related to EHR MedRec unearthed by this study: 1) there was an absence of shared understanding among practitioners, of the value of EHR MedRec in promoting patient safety, which contributed to workarounds, and suboptimal use of the EHR MedRec system; and 2) there was a socio-technical dimension to many of the issues, creating an added layer of complexity. These gleanings in turn, provide insights into best practices for managing both: 1) clinical transitions-of-care in the EHR MedRec process; and 2) socio-technical challenges encountered in EHR MedRec implementation.